Peranan Pendekatan Psikodrama dalam Meningkatkan Kepercayaan Diri Siswa - Suci Amelia Mardiah; Yeni Karneli; Netrawati Netrawati (Politeknik Kampar, 2025)
This study aims to systematically review the effectiveness of the psychodrama approach in increasing students' self-confidence. The psychodrama approach emphasizes role-playing, spontaneity, and exploration of emotional experiences in social groups. The Systematic Literature Review (SLR) method was used by collecting 20 scientific articles from various international databases (Google Scholar, Springer, Wiley, ProQuest, ResearchGate) in the period 2015–2025. The selection process was carried out through strict inclusion and exclusion criteria, as well as thematic analysis. The results showed that psychodrama had a positive effect on reducing social anxiety, increasing self-expression and validation, and strengthening students' social interactions. The theoretical and practical implications of these findings indicate that psychodrama is a potential intervention approach to be applied in formal educational settings.